First Molecular Genetic Characterization of Skene's Gland Adenocarcinoma - Lenz, Jiří; Michal, Michal; Michal, Michael; Hes, Ondřej; Konečná, Petra; Lenz, David (International journal of surgical pathology, 2021)
Primary urethral adenocarcinomas are very rare neoplasms accounting for <10% of all urethral carcinomas. Site of their origin is unclear, but they seem to arise from Skene's paraurethral glands, which is the female homologue of the male prostate. The aim of this article is to report the first case of Skene's gland adenocarcinoma in which a molecular genetic profiling was performed. The patient was a 73-year-old woman with a polypoid lesion sized 3 × 2 cm located at the interface between the bladder neck and the proximal urethra. Transurethral resection was performed and small tissue fragments with positive margins were obtained. Histology revealed an epithelial neoplasm consisting of cribriform structures located in the subepithelial connective tissue of the bladder wall and proximal urethra. The lesion showed positive immunohistochemical staining with prostate specific antigen, prostatic acid phosphatase, NKX3.1, and alpha-methylacyl-CoA racemase. Using the Illumina TruSight Tumor 170 next-generation sequencing assay, a mutation and loss of heterozygosity of the phosphatase and tensin homologue (PTEN) gene was detected. No fusion in any of the examined genes was found using this assay as well as FusionPlex Solid Tumor Kit and FusionPlex Sarcoma kit assays from ArcherDX. Given the rarity of Skene's gland adenocarcinoma, it is uncertain whether the same grading and prognostic criteria that are currently used for prostatic cancer apply here as well. It is also unclear what treatment strategy should be applied, but according to the available literature, it seems that local excision or wide surgical resection could represent sufficient therapeutic modalities.
Keywords: senioři; PTEN gene; fosfohydroláza PTEN; Urethra; next-generation sequencing; molecular genetics; mutace; adenokarcinom; PTEN Phosphohydrolase; Loss of Heterozygosity; Urethral Neoplasms; Biomarkers, Tumor; ztráta heterozygozity; uretra; ženské pohlaví; nádorové biomarkery; Mutation; Humans; Skene’s gland adenocarcinoma; paraurethral glands; nádory močové trubice; Female; Aged; Adenocarcinoma; lidé